Pengaruh Laba Akuntansi dan Arus Kas Operasi Terhadap Return Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Dewi Rahmawati (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This study aims to determine the effect of accounting earnings and operating cash flow in partial, simultaneous, and the most dominant variables that influence on stock returns in companies listed on the Jakarta Islamic Index. The research method used is associative quantitative. The analysis technique is multiple regression analysis. This research was conducted using a selected sample of 16 companies registered in the Jakarta Islamic Index for the 2014-2017 period, so that the research data from 64 annual financial reports. Data collection is done by means of documentation that is taking from the internet and literature. Based on the results of research that was tested through a t test or partially by the SPSS test it was concluded that accounting profit and operating cash flow affect stock returns. For the F test it was concluded that accounting earnings and operating cash flows simultaneously affect stock returns. The test results of the most dominant variable are accounting earnings because the significance value is close to zero and shows the greatest beta value.